The validity and reliability of professional learning community instruments in small schools peninsular Malaysia - Mohd Norlizam Mohd Razali; Aida Hanim A. Hamid; Bity Salwana Alias (Institute of Advanced Engineering and Science, 2024)
A professional learning community (PLC) instrument was developed to determine the level of PLC practice in small schools in Peninsular Malaysia. This study was conducted in Perak and Negeri Sembilan to determine the instrument's reliability and validity. Exploratory factor analysis (EFA) and item reliability analysis were used to determine the questionnaire’s reliability and validity. Next, the average congruence percentage (ACP) is used to determine the reliability test between expert assessors. Experts approved the validity and reliability of the instrument before the EFA test was conducted. All five constructs have high-reliability index values between 0.86–0.95. Next, the EFA analysis shows five dimensions in the PLC instrument with factor loadings ranging from 0.61–0.84. The findings also show that the variance explained in the data is 68.99% with an Eigenvalue greater than 1. This result indicates that all items are received with high approval. In addition, a very high-reliability coefficient value, α=0.96. The results prove that this PLC instrument has high validity and reliability and can measure the level of PLC implementation practices in small schools in Peninsular Malaysia.